Subjective assessment of patients regarding the attitude of the medical staff of primary health care in the light of satisfaction with medical services - Strzelecka, Agnieszka; Nowak-Starz, Grażyna (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Introduction. The patient’s subjective assessment of the quality of medical services is affected by the level of performance of medical services, including the assessment of the atmosphere at the site of the service and the evaluation of the medical staff. Aim of the study. Examining the subjective assessment of patients on the attitude of the medical staff of primary health care in light of satisfaction with medical services. Material and methods. The study included 422 primary care patients in the Świętokrzyskie region. When making a statistical analysis c2 test, Fisher test and logistic regression model were used. The level of significance of the test was a < 0.05. Results. The surveyed patients indicated that satisfaction with medical services is affected by the course of the visit — a sincere and friendly conversation (69,91%), a positive attitude of a doctor to the patient (60,90%) and the attitude of the other medical staff — nurses. The parameters in the logistic regression model for the variables attitude of the doctor to patient, a way of greeting are significant at p < 0.001, and the ratio of the nurses at p = 0.002. The results of logistic regression analysis showed that these variables were significantly associated with a positive quality of medical services. Conclusions. Based on the study it can be concluded that the subjective assessment of patients regarding the attitude of medical staff of POZ in the light of satisfaction with medical services is significantly affected by the course of medical visits, the way of doctor and nurses behavior towards the patient.